The upside of your dark side : why being your whole self--not just your "good" self--drives success and fulfillment - Kashdan, Todd B.; Biswas-Diener, Robert (Hudson Street Press, 2014)
"In The Upside of Your Dark Side, two pioneering researchers in the field of psychology show that while mindfulness, kindness, and positivity can take us far, they cannot take us all the way. Sometimes, they can even hold us back. Emotions such as anger, anxiety, guilt, and sadness might feel uncomfortable, but it turns out that they are also incredibly useful. For instance: - Anger fuels creativity - Guilt sparks improvement - Self-doubt enhances performance - In the same vein, we can become wiser and more effective when we harness the darker parts of our personality in certain situations. For instance: - Selfishness increases courage - Mindlessness leads to better decisions - The key lies in what the authors call "emotional, social, and mental agility," the ability to access our full range of emotions and behavior-not just the "good" ones-in order to respond most effectively to whatever situation we might encounter. Drawing on years of scientific research and a wide array of real-life examples including sports, the military, parenting, education, romance, business, and more, The Upside of Your Dark Side is a refreshing reality check that shows us how we can truly maximize our potential. With an appreciation of our entire psychological toolkit, we become whole-which allows us to climb the highest peaks and handle the deepest valleys"--